Modulation of SIRT1/PPAR? pathways and tight junction proteins by nicotinamide riboside under chronic variable stress - Celik, Abdullah; Şahin, Nurhan; Orhan, Cemal; Er, Besir; Erten, Fusun; Ozmen, Busra; Şahin, Kazım (Springer, 2026)
Chronic stress disrupts homeostasis, leading to major health problems such as liver damage, intestinal barrier dysfunction, and impaired glucose metabolism. Although current treatments, including anxiolytics, sedatives, antidepressants, and beta blockers, are effective, their adverse effects emphasize the need for safer alternatives. Nicotinamide riboside (NR), a precursor of nicotinamide adenine dinucleotide (NAD+), plays a central role in energy metabolism and oxidative stress regulation; elevated NAD + levels have been associated with reduced risk of chronic diseases such as obesity and type 2 diabetes. However, the effects of NR on liver metabolism, intestinal barrier integrity, and related protein pathways remain unclear. This study investigated the effects of NR supplementation in rats exposed to chronic variable stress (CVS). Fifty-six male Sprague Dawley rats were divided into normal and CVS groups and treated in a 2 x 4 factorial design with 0, 150, 300, or 600 mg/kg NR. Under CVS conditions, serum glucose, corticosterone, ACTH, and insulin levels increased, whereas NAD+, NADPH, nicotinamide (NAM), and nicotinic acid (NA) decreased significantly (p < 0.001). NR supplementation effectively corrected these biochemical imbalances and upregulated hepatic markers, including PPAR gamma, SIRT1, GLUT2, IRS1, and FASN (p < 0.001). Furthermore, the increased expression of key transport proteins such as PepT1, LAT2, EAAT3, FABP2, and FATP4 contributed to maintaining intestinal barrier integrity and improving gut health. NR also promoted the recovery of tight and adherens junction proteins. Notably, high-dose NR (600 mg/kg) markedly alleviated liver fibrosis, improved glucose metabolism, and strengthened intestinal barrier function, demonstrating its therapeutic potential as an alternative strategy against stress-induced metabolic disorders.Key points center dot NR mitigated chronic stress-induced liver, intestinal, and glucose dysregulation.center dot NR improved glycemia and NAD(+)-related biomarkers under stress.center dot NR reduced hepatic fibrosis markers.center dot NR strengthened TJ/AJ proteins, supporting intestinal barrier integrity.center dot Findings support NR's therapeutic potential in stress-related metabolism.
Keywords: Stress; Nicotinamide riboside; Liver; Gut